Metabolomics reveal changes in flavor quality and bioactive components in post-ripening Torreya grandis nuts and the underlying mechanism. (16th April 2023) - Suo, Jinwei; Ma, Zhenmin; Zhao, Bing; Ma, Shuang; Zhang, Zuying; Hu, Yuanyuan; Yang, Baoru; Yu, Weiwu; Wu, Jiasheng; Song, Lili
Graphical abstract: Highlights: Metabolic profiles in the post-ripening T. grandis nuts were identified. Secondary metabolites accounted for about 60% of the total DAMs. DAMs are mainly belonging to terpenoids, flavonoids, coumarins and phenolic acids, etc. Functions of DAMs include nut flavor and quality formation, as well as other bioactive compounds. Abstract: Secondary metabolites are a group of small molecules with critical roles in plants fitness in addition to their potential bioactivities in humans. Most of these compounds are associated with the flavor and quality formation of fruits or nuts during the development or the postharvest stages. Change in metabolic profiles and shifts underpinning the post-ripening process in T. grandis nuts are not yet reported. In this study, a large scale untargeted metabolomics approach was employed in T. grandis nuts, revealing for a total of 140 differential accumulated metabolites. Among them, nearly 60% of metabolites belonging to terpenoids, coumarins and phenolic acids, and phytohormones were showed a gradual accumulation pattern, while most of compounds in flavonoids were decreased during post-ripening. An in-depth analysis of changes in these metabolite classes suggest a framework for post-ripening process effect associated with the postharvest quality of T. grandis nuts for the first time.